1995
DOI: 10.1111/j.1460-9568.1995.tb00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Modulation of Inferior Olivary Oscillations and Synchronicity: A Multiple‐electrode Study in the Rat Cerebellum

Abstract: Simultaneous recording of complex spikes from multiple Purkinje cells (up to 44) in the rat cerebellum was used to examine the effects of 5-hydroxytryptamine (serotonin, 5-HT) on olivocerebellar function. Microinjection into the inferior olive was found to increase the average firing rate of inferior olivary neurons while slowing their oscillation frequency and increasing the coherence of their oscillations. Indeed, while the normal rostrocaudal band of synchronous activity remained unchanged, the degree of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 47 publications
5
85
0
1
Order By: Relevance
“…Previous work on CSs in the cerebellar cortex has described zero-phase synchrony between PC pairs (26)(27)(28)(29). Our study extends these results to stable, nonzero-phase differences.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous work on CSs in the cerebellar cortex has described zero-phase synchrony between PC pairs (26)(27)(28)(29). Our study extends these results to stable, nonzero-phase differences.…”
Section: Discussionsupporting
confidence: 77%
“…In this experiment, oscillation frequency was Ϸ8.6 Hz on all 15 electrodes that exhibit oscillatory activity. Across experiments (n ϭ 13), stable oscillation frequency was in the range of 4-11 Hz with 1 exception (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Within each experiment, oscillation frequency was similar across electrodes, and occasional epochs of frequency deviation ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…However, Maura et al (1988) have shown that endogenous release of glutamate in the cerebellum was inhibited by the 5-HT 2 receptor agonist DOI, which was reversed by the selective 5-HT 2 receptor antagonist ketanserin. Through the use of 5-HT and various agonists and antagonists, the expression of 5-HT 2A R has also been demonstrated in Purkinje cells (Sugihara et al 1995), which is in agreement with the staining results with our MAb. We do not presently know the reason for this discrepancy.…”
Section: Discussionsupporting
confidence: 76%
“…Autocorrelation and cross-correlation histograms with a time bin of 1 msec were plotted for SS firing from single and paired PCs, respectively. The strength of the oscillation was quantified with a rhythm index (RI) introduced by Sugihara et al (1995). Briefly, peaks and valleys were recognized if their heights and depths exceeded the mean baseline level Ϯ SD (measured at time lags of 250 -300 msec).…”
Section: Methodsmentioning
confidence: 99%